Promoting an Appreciation for Diversity Through Reading Literary Works to Prevent Radicalism - Yunidar Yunidar; Gusti Ketut Alit Suputra; Anjar Kusuma Dewi (Ranah: Jurnal Kajian Bahasa, 2024)
This study aims to identify the factors of prejudice that can lead to radicalization among elementary school students and to improve understanding of the values of diversity and tolerance through academic literacy. This study was conducted in elementary schools in Palu City involving 500 students who were divided into two groups: experimental and control. The research method used was descriptive research with a quasi-experimental design, where both groups were given pre- and post-tests to measure the increase in attitudes of respect and tolerance. Data were collected through test instruments that measured students' moral attitudes towards diversity and radicalization, while data analysis techniques used descriptive statistics and hypothesis testing. The results showed that the experimental group that participated in the "Baku Sayang and Baku Jaga" program experienced a significant increase in respect and tolerance values. The N-gain score for respect in the experimental group increased by 0.79 (high category), and for tolerance increased by 0.82 (high category), while the control group only showed a moderate increase with N-gain scores of 0.33 and 0.35, respectively. The findings confirm that the program is effective in increasing students’ respect and tolerance which can reduce the potential for radicalization among them. This study suggests that academic literacy-based approaches and discussion groups are effective strategies to support character education in elementary schools. AbstrakPenelitian ini bertujuan untuk mengidentifikasi faktor-faktor prasangka yang dapat menyebabkan radikalisasi di kalangan siswa sekolah dasar serta untuk meningkatkan pemahaman tentang nilai-nilai keberagaman dan toleransi melalui literasi akademik. Penelitian ini dilaksanakan di sekolah dasar Kota Palu dengan melibatkan 500 siswa yang dibagi menjadi dua kelompok: eksperimen dan kontrol. Metode penelitian yang digunakan adalah penelitian deskriptif dengan desain kuasi-eksperimental, di mana kedua kelompok diberi tes pra dan pasca untuk mengukur peningkatan sikap menghormati dan toleransi. Data dikumpulkan melalui instrumen tes yang mengukur sikap moral siswa terhadap keberagaman dan radikalisasi, sedangkan teknik analisis data menggunakan statistik deskriptif dan uji hipotesis. Hasil penelitian menunjukkan bahwa kelompok eksperimen yang mengikuti program “Baku Sayang dan Baku Jaga” mengalami peningkatan yang signifikan pada nilai rasa hormat dan toleransi. Skor N-gain untuk rasa hormat pada kelompok eksperimen meningkat sebesar 0,79 (kategori tinggi), dan untuk toleransi meningkat sebesar 0,82 (kategori tinggi), sementara kelompok kontrol hanya menunjukkan peningkatan yang moderat dengan skor N-gain masing-masing 0 ,33 dan 0,35. Temuan ini menegaskan bahwa program ini efektif dalam meningkatkan sikap menghormati dan toleransi siswa yang dapat mengurangi potensi radikalisasi di kalangan mereka. Penelitian ini menyarankan bahwa pendekatan berbasis literasi akademik dan kelompok diskusi merupakan strategi yang efektif untuk mendukung pendidikan karakter di sekolah dasar.